(In)visibles (2022)
Soil contamination by heavy metals has been identified as one of the main threats to soil. Its implications include a negative effect on the environment and put food safety at risk. The high toxic levels of heavy metals found in soil decrease the quantity, quality, and safety of food, producing dangerous crops for animal and human consumption. This generates health issues to people including cancer, adverse effects on the nervous, respiratory, reproductive, and cardiovascular systems. In Colombia, the farming community of Mochuelo Alto is located next to the landfill of Bogota. This community, deeply affected by soil contamination, loses approximately 50% of its production per harvest due to the reduction of quality and low productivity of their crops obtaining economic losses. The community is also uncertain about the condition of their water and soil, considering that this problem is caused by landfill´s leachate, which contains high levels of heavy metals. Despite the proximity and exposure to the sources of pollution, this population has limited access to pollution remediation technologies. Science has developed several remediation biotechnologies, which in some cases have remained in scientific publications, due to several application challenges, highlighting a distance between science and the public. First, a great deal of funding is required to carry out metal characterization studies in the affected areas. Second, expensive, and specialized equipment is needed to measure metals, as well as professionals with expertise in the field. Finally, biotechnology faces a challenge of scalability as it is necessary to know the specific type of contaminant for each area to estimate the capacity of the microorganism. The project approaches this problem from biodesign, joining science and design to reduce the uncertainty that farmers have about the contamination of their crops, explaining the causes and consequences of the issue, and relating water remediation biotechnology with the community for them to have a broader perspective on the impact it has on society. The aim is to reduce heavy metal contamination by means of an "in situ" and portable system that incorporates bioremediation biotechnology (Lysinibacillus sphaericus CBAM5), to capture heavy metals in the contaminated water sources of the farmers of Mochuelo Alto. A strategy was also designed to make heavy metal contamination visible and explain the relationship with the bacteria Lysinibacillus sphaericus CBAM5, with the aim that the community interacts and relates to the biotechnology. This allows the community to understand the impact and functioning of the microorganism, to generate dialogues on the implications of the problem.